2000
DOI: 10.1034/j.1600-0722.2000.108005456.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive bonding of titanium with a thione‐phosphate dual functional primer and self‐curing luting agents

Abstract: A consistent bond between the metal framework and the luting agent is desired when resin-bonded prostheses are constructed with titanium. The purpose of this study was to evaluate three different metal primers on titanium bonding. Two sources of titanium (machined 99.9% titanium and cast Titan Ingot JS2) were used. Disk specimens were bonded with eight combinations of three primers and two luting agents (Panavia 21 and Super-Bond C&B), including two controls. Shear bond strengths were determined after 24-h wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 3 publications
3
41
0
2
Order By: Relevance
“…These findings agreed with previous studies which reported that an MDP-containing primer improved the adhesive bonding between titanium and resins 15,16) . It was suggested that the phosphoric acid group of MDP monomer was effective in improving the adhesion of resins to titanium 20) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings agreed with previous studies which reported that an MDP-containing primer improved the adhesive bonding between titanium and resins 15,16) . It was suggested that the phosphoric acid group of MDP monomer was effective in improving the adhesion of resins to titanium 20) .…”
Section: Discussionsupporting
confidence: 83%
“…To improve the adhesive bonding of resins to titanium, several physical and chemical surface modification techniques were investigated: sandblasting 10) , silica coating [11][12][13] , application of adhesive primers [14][15][16][17][18][19][20][21] , plasma irradiation 22) , alkaline treatment 23,24) , and acid etching 25,26) . On the use of adhesive monomers in primers, the authors previously reported that a primer containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomer promoted resin bonding to titanium 14) .…”
Section: Introductionmentioning
confidence: 99%
“…This commercially available dual function primer was said to be effective for both noble and base metal alloys [38,39]. In current study, MDP-containing metal primer showed higher bond strength than other sulfur-containing metal primers when it was used on the untreated zirconia ceramics.…”
Section: Discussionmentioning
confidence: 62%
“…Other previous studies have already shown that a durable resin bond strength to Y-TZP ceramics is achieved only after air abrasion and using resin composite cements containing a special MDP monomer [6,28,39,[40][41][42][43]. This is because the MDP monomer bonds directly to metal oxides [27,38].…”
Section: Discussionmentioning
confidence: 99%
“…One primer (Alloy Primer, Kuraray Medical Co. Ltd., Tokyo, Japan) 27) contained VBATDT and 10-methacryloxydecyl dihydrogen phosphate (MDP), and another primer (Metal Link, Shofu Inc., Kyoto, Japan) contained 10-MDDT and 6-methacryloxyhexyl phosphonoacetate (6-MHPA) 28) . Although these dual-function primers were effective for both noble and base metal alloys [29][30][31] , limited information is available regarding primers with other combinations of sulfur-containing monomers and phosphate monomers 32) . The purpose of the present study, therefore, was to investigate the effects of modifying a thiouracil primer with phosphate monomers on bond strength between a self-curing luting resin and Ag-Pd-Au alloy and on the bonding durability of these primers against thermocycling stress.…”
Section: Introductionmentioning
confidence: 99%